NHC-Copper-Catalyzed Tandem Hydrocupration and Allylation of Alkenyl Boronates - Jang, Won Jun; Han, Jung Tae; Yun, Jaesook (Synthesis, 2017)
A tandem hydrocupration/allylation of alkenyl boronates efficiently proceeds with NHC-copper catalysts using hydrosilane and allyl phosphate as reagents. In the presence of IMes–Cu catalyst, the allylation of in situ generated Β-α-copper intermediates smoothly occurs to give homoallylic boronates in high yields, despite competitive side reaction pathways. Mono- and disubstituted alkenyl boronates were effective in the reaction with terminal allyl phosphates, but trisubstituted substrates showed limited reactivity.
Keywords: allylic substitution; copper; homoallylic boronates; hydrocupration; N-heterocyclic carbenes; tandem reaction